Проблеми визначення сутності житлово-комунальних послуг як специфічних суспільних благ та специфічного об’єкта економічного контролю - Головченко, О. О.; Головченко, Н. Ю.; Holovchenko, O.; Holovchenko, N. (КНТУ, 2015)
Публікація присвячена дослідженню існуючих у вітчизняному науковому середовищі поглядів на сутність житлово-комунальних послуг як специфічних суспільних благ. В статті системно розглянуті популярні на сьогодні підходи щодо визначення житлово-комунальних послуг як товару, як послуги, а також варіанти комбінованої ідентифікації. На підставі уточнення сутності житлово-комунальних послуг як специфічних суспільних благ, розглянута доцільність перегляду законодавчого визначення відповідних послуг. The purpose of this article is to identify the main problems in determining the nature of housing and communal services as specific public benefits; to define the place of these services in the system of social-economic relations and to formulate on this basis rational objects of economic control as a management function of process providing housing and communal services. We have researched different views available in domestic scientific area on the essence of housing and communal services as a specific public benefits etc.
Problems of Determining the Nature of Housing Services as a Specific Public Benefits and Specific Object of Economic Control
Keywords: житлово-комунальне господарство; житлово-комунальні послуги; Житлово-комунальний кодекс; housing and utilities sector; housing and communal services; housing and communal code